Інноватика в освіті – шлях до її якості, досвід США - Гаращук, Олена; Куценко, Віра (Видавництво Львівської політехніки, 2015)
Наголошено на зростаючій функції освіти в соціально-економічному розвитку, в формуванні інноваційної економіки. Розкривається сутність інноватики, основні напрями інноваційної діяльності. Подається взаємозв'язок розвитку науково-технічного прогресу та інноваційної діяльності вищих навчальних закладів, наводиться в цьому аспекті досвід США, зокрема і щодо розвитку дослідницьких і підприємницьких університетів. Обґрунтовуються способи підвищення якості освіти, зокрема й за рахунок використання досвіду США. Stresses the increasing role of education in economic and social development in the formation of an innovative economy. The essence of innovation, the main directions of innovation. Describes the relationship of scientific and technological progress and innovation of higher education institutions is given in this respect the experience of the United States, including the development of research and entrepreneurial universities. Substantiates ways to improve the quality of education, including through the use of the US experience.
Information and innovation component new educational paradigm
Keywords: інноваційна діяльність; інноватика; дослідницький університет; рейтинг; якість освіти; інноваційний потенціал; innovation activity; Innovation; research university; the quality of education; innovation potential